Three‐dimensional P wave azimuthal anisotropy in the lithosphere beneath China. Issue 7 (17th July 2014) - Huang, Zhouchuan; Wang, Pan; Zhao, Dapeng; Wang, Liangshu; Xu, Mingjie
Abstract Seismic anisotropy in the upper mantle beneath East Asia has been studied extensively using shear wave (SKS) splitting measurements, which have provided important information on mantle dynamics in this region. However, SKS measurements have poor vertical resolution, and so their interpretations are usually not unique. In this work we use a large number of traveltime data from 34, 036 local earthquakes recorded by 1563 seismic stations to determine the first model of 3‐D P wave azimuthal anisotropy in the lithosphere beneath China. Our results show that the fast velocity directions (FVDs) are generally correlated with the surface geologic features, such as the strikes of the orogens, active faults, and tectonic boundaries. The FVDs in the upper crust are normal to the maximal horizontal stress (σH) in regions with extensive compression such as the Tibetan Plateau, whereas they are subparallel to σH in strike‐slip shear zones such as the western and eastern Himalayan syntax. The comparison of the FVDs of P wave anisotropy with SKS splitting measurements indicates that beneath the Tibetan Plateau the seismic anisotropy in the lithosphere contributes significantly to the SKS splitting observations. In contrast, in east China the P wave FVDs in the lithosphere are different from the SKS splitting measurements, suggesting that the SKS splitting is mainly caused by the anisotropy in the deeper mantle such as the asthenosphere and the mantle transition zone under east China. These novel results provide important new information on the lithospheric deformation and mantle dynamics in East Asia.